In vivo interactions between myosin XI, vesicles and filamentous actin are fast and transient in Physcomitrella patens - Bibeau, Jeffrey P. (J Cell Sci, 2020)
The actin cytoskeleton and active membrane trafficking machinery are essential for polarized cell growth. To understand the interactions between myosin XI, vesicles and actin filaments in vivo, we performed fluorescence recovery after photobleaching and showed that the dynamics of myosin XIa at the tip of the spreading earthmoss Physcomitrella patens caulonemal cells are actin-dependent and that 50% of myosin XI is bound to vesicles. To obtain single-particle information, we used variable-angle epifluorescence microscopy in protoplasts to demonstrate that protein myosin XIa and VAMP72-labeled vesicles localize in time and space over periods lasting only a few seconds. By tracking data with Hidden Markov modeling, we showed that myosin XIa and VAMP72-labeled vesicles exhibit short runs of actin-dependent directed transport. We also found that the interaction of myosin XI with vesicles is short-lived. Together, this vesicle-bound fraction, fast off-rate and short average distance traveled seem be crucial for the dynamic oscillations observed at the tip, and might be vital for regulation and recycling of the exocytosis machinery, while simultaneously promoting vesicle focusing and vesicle secretion at the tip, necessary for cell wall expansion.